Phytochemical analysis and in vivo toxicity evaluation of green vegetable Tetrastigma angustifolia (Roxb.) leaves - Junejo, Julfikar Ali; Singh, Kh.Herojit; Islam, Johirul; Mondal, Prodyut; Hussan, Nazim; Zaman, Kamaruz (Asian Journal of Biological and Life Sciences, 2016)
T. angustifolia (Vitaceae) is a Green vegetable and valuable ethnomedicinal plant in India and inflorescence has been reported for the treatment of antioxidant in Indian literatures. The present study intended with various phytochemical, physicochemical screening and toxicity studies were carried out on the leaves of the T. angustifolia. Phytochemical evaluation of extracts of revealed that the presence of flavonoids, glycosides, alkaloids, proteins and phenolic compounds. Physicochemical properties including total ash, water soluble ash, acid insoluble ash and loss on drying were determined. The toxicity studies were performed as acute oral toxicity determined the highest dose of 5000 mg/kg body weight 2 weeks. The results of the various phytochemical, physicochemical and toxicity tests indicated that the plant to be rich in various biologically active compounds which could serve as potential source of the crude drugs and in addition the plant is not toxic to the experimental model.
Keywords: Tetrastigma angustifolia; phytochemical screening; physicochemical evaluation; Toxicity studies.